2018
DOI: 10.1631/jzus.b1700095
|View full text |Cite
|
Sign up to set email alerts
|

Assessments of tear meniscus height, tear film thickness, and corneal epithelial thickness after deep anterior lamellar keratoplasty

Abstract: Patients with keratoconus tend to have a thinner central corneal epithelium. Corneal epithelium keeps regenerating over time after DALK. DALK did not induce a significant change in tear volume compared with the fellow eye. Postoperative tear function might depend on an individual's general condition, rather than on age, gender, bed/graft size, time following surgery, or residual sutures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Given that the endothelium can be regenerated on the donor graft, it is important to expand the donor source, and, given that the regenerated endothelium is derived from the host itself, there will be no immunoreactions targeting the donor endothelium and no graft failure caused by endothelial rejection after PKP [ 16 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that the endothelium can be regenerated on the donor graft, it is important to expand the donor source, and, given that the regenerated endothelium is derived from the host itself, there will be no immunoreactions targeting the donor endothelium and no graft failure caused by endothelial rejection after PKP [ 16 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, the TMR is indicative not only of tear volume at the TM but also of the total tear volume over the OS, and it is theoretically also associated with the aqueous layer thickness of the PCTF [6,7]. Indeed, it is clinically shown that a significant correlation exists in vivo between TMR and total tear volume [30], tear film thickness [6,31,32], and stability [4,[33][34][35]. Thus, TMR is implemented as an overall indicator of PLTF quality.…”
Section: Subjectsmentioning
confidence: 99%